Epigenetic silencing of TMEM176A activates ERK signaling in human hepatocellular carcinoma - Hongxia Li; Meiying Zhang; Enqiang Linghu; Fuyou Zhou; James G. Herman; Liming Hu; Mingzhou Guo (Clinical Epigenetics, 2018)
Abstract Background The role of TMEM176A in human hepatocellular carcinoma (HCC) is unknown. This study explored the epigenetic regulation and function of TMEM176A in human HCC. Materials and methods Twelve HCC cell lines and 126 cases of primary cancer were analyzed. Methylation-specific PCR, immunohistochemistry, flow cytometry, and xenograft mouse models were employed. Results TMEM176A was highly expressed in SNU387, SNU182, Huh1, and SNU475 cells; reduced expression was observed in HepG2 and PLC/PRF/5 cells; and no expression was found in SNU449, HBXF344, SMMC7721, Huh7, and LM3 cells. Unmethylation of the TMEM176A promoter was detected in SNU387, SNU182, Huh1, and SNU475 cells; partial methylation was observed in HepG2 and PLC/PRF/5 cells; and complete methylation was found in SNU449, HBXF344, SMMC7721, Huh7, and LM3 cells. Upon treatment with 5-Aza-2-deoxycytidine, re-expression of TMEM176A was detected in SNU449, HBXF344, SMMC7721, Huh7, and LM3 cells; increased expression of TMEM176A was observed in HepG2 and PLC/PRF/5 cells; and no expression changes were found in SNU387, SNU182, Huh1, and SNU475 cells. The TMEM176A promoter region was methylated in 75.4% (95/126) of primary human HCC. Reduced expression of TMEM176A was associated with promoter region methylation (P < 0.05). No association was found between TMEM176A promoter methylation and age, gender, HBV infection, liver cirrhosis, tumor size, lymph node metastasis, vessel cancerous embolus, number of lesions, and TNM stage (all P > 0.05). These results demonstrated that the expression of TMEM176A is regulated by promoter region methylation. Methylation of the TMEM176A promoter was significantly associated with tumor cell differentiation (P < 0.05) and was an independent prognostic factor for poor 3-year overall survival (OS, P < 0.05). TMEM176A expression induced cell apoptosis; inhibited cell proliferation, migration, and invasion; suppressed human HCC cell xenograft growth in mice; and inhibited ERK signaling in HCC cells. Conclusion The promoter region of TMEM176A is frequently methylated in human HCC, and the expression of TMEM176A is regulated by promoter region methylation. Methylation of the TMEM176A promoter may serve as a diagnostic and prognostic marker in HCC. TMEM176A suppresses HCC growth by inhibiting the ERK signaling pathway.